PERLINDUNGAN HUKUM BAGI PEKERJA ALIHDAYA DENGAN UPAH DIBAWAH KETENTUAN: TINJAUAN TEORI KEPASTIAN HUKUM - Kurnia, Asep (Universitas Muhammadiyah Ponorogo, 2024)
Outsourcing is to respond to global economic developments and the speed of technological development so that global competition is very tight. The logical consequence of this condition is the decision by company leaders or management to hand over or outsource some of the company's processes to other parties. The aim of this research is the implementation of Law Number 11 of 2020 concerning Job Creation in relation to providing protection for outsourcing workers. This type of research is qualitative, with a normative legal research approach. The results of the discussion obtained the answer that legal protection for outsourced workers is viewed from the principle of legal certainty in Law Number 13 of 2003 and Law Number 11 of 2020 on Job Creation concerning Employment which can be seen in two forms, namely legal certainty in preventive protection and legal certainty in repressive protection. Legal certainty in the context of preventive protection covers several aspects, including clarity regarding employment relations, time-limited work agreements (PKWT), social security, wage levels and wage compensation. In the context of outsourcing, there are no longer any restrictions on the types of work that can be outsourced. For this reason, regulations are needed that provide further detail regarding legal certainty in preventive and repressive protection, to ensure more comprehensive protection.